LET’S GET ONE THING STRAIGHT, THEY’RE NOT: THE APPOINTMENT OF THE FIRST OPENLY GAY FEDERAL JUDGES - Hon. Willie J. Epps, Jr.; Katalin M. Minkler (Washington University Journal of Law and Policy, 2024)
In this Article, Judge Epps and Ms. Kaitlin Minkler collect an unrivaled amount of information about the first openly gay judges confirmed for life to federal courts of general jurisdiction in the United States. The Article references interviews with the judges about their trailblazing journeys. It examines the experiences of these twenty-two judges as they shape the judiciary from within and inspire future generations of LGBTQIA+ lawyers.
Keywords: Gay; Judges; LGBTQIA+; Federal Courts